Constructions of Cancer among Survivors in Bandung Society - Amalia Djuwita; Deddy Mulyana (MediaTor (Jurnal Komunikasi), 2019)
People assume that cancer is a deadly disease. The communication gap between physicians and their patients results in incomplete information obtained by people with cancer. This research was conducted using a qualitative approach in order to explore the meaning of cancer within Bandung Cancer Society. Theories used as references are phenomenology and symbolic interactionism. The results of the study of 10 informants indicated that cancer is a very frightening disease; cannot be cured and results in no hope of survival; cancer is caused by unhealthy life style; and yet cancer increases acts of worship. All informants as cancer survivors made efforts to survive by following the doctor’s advice. Another result of this study states that communication that takes place between cancer survivors and other people with cancer within the Bandung Cancer Society has managed to change the view of cancer, motivate and raise the spirit of life.